Effect of tillage practices and cropping systems on growth and yield of maize grown in sequence with wheat and chickpea - Parihar, M.D.; Nanwal, R.K.; Kumar, Pawan; Kumar, Satish; Singh, A.K.; Chaudhary, V.; Parmar, H.; Jat, M.L. (Annals of Agricultural Research, 2016)
Field experiments were conducted at New Delhi during the kharif season of 2012 and 2013 with maize-wheat/Chickpea cropping systems to evaluate the effect of different tillage and crop establishment techniques, and residue management on performance of the maize grown in sequence with wheat and chickpea in terms of growth and yield. The results revealed that performance of maize in terms of two years mean growth parameters, yield attributes and yields were influenced significantly under different tillage and crop establishment techniques. ZT flat planting with residue retention resulted in significantly higher mean plant height (174.95 cm), dry matter accumulation, leaf area and leaf area index (LAI) than conventional till flat planting of maize. Mean values of days to 50% silking, days to maturity of maize were minimum in zero till flat planting under residue retention with maximum cobs/m2 (7.75). The mean maize yield attributes viz; cob length, cob girth and grain rows/cob were not significantly influenced due to the tillage practices, residue retention and cropping systems, however, the grains/cob was significantly influenced by tillage practices and residue retention. The cob, grain and stover yields are also significantly influenced by tillage practices and residue retention and these were maximum under zero till flat planting with residue retention. The two years mean cob, grain and stover yields of maize were 16.70, 23.37 and 16.17% higher under zero till flat planting with residue retention than to conventional till without residue planting.